Microwave-Assisted Syntheses of Thiophene-Based Ionic Liquids: Structural Design and Optimization - Schiel, María A.; Domini, Claudia E.; Chopa, Alicia B.; Silbestri, Gustavo F. (Synthesis, 2018)
This manuscript explores microwave-assisted reactions for the synthesis of new ionic materials involving the S-alkylation of thiophene. All isolatable products have been fully characterized by NMR and all product have been quantified through UV-vis spectroscopy. By means of a design technique, the experimental protocol (25 min, 200 W, 50 °C) has been optimized, which led us to better yields (96 %). In the absence of MW activation, the conventional thermal reaction at room temperature took longer (24 – 48 h) to obtain similar results.
Keywords: thiophenium salt; ionic liquid; syntheses; microwave; experimental design